HUBUNGAN DUKUNGAN SOSIAL ORANG TUA TERHADAP PENYESUAIAN DIRI MAHASISWA TAHUN PERTAMA FAKULTAS KEPERAWATAN - Sintia Adwi Pama Putri; Jumaini Jumaini; Misrawati Misrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Adjustment is important for the first year students, if students are not able to adjust to their new learning environment, there will be potential for many problems because the first year students are faced with various changes and differences in various aspects of life. Adjustment to the first year students will be easier if there is a family role such as social support from family members, one of them is parents.  This study aims todetermine the relationship between parents’ social support to the adjustment of first year students at the Faculty of Nursing. Respondents of this study were 89 students in the first year at the Faculty of Nursing selected based on inclusion and exclusion criteria with purposive sampling techniques. The questionnaire in this study was a modification of Rohmah's research (2017) and Buamona (2020). The results of the study were obtained by the majority of respondents aged 19 years (65.2%) and most of the female sex (91%). The results of the data analysis using the Chi-Square test obtained the value of p value 0.548> α (0.05). There is no significant relationship between parents' social support and the adjustment of the first year students at the Faculty of Nursing. Based on the results of the study, it is recommended to nursing students who get low social support to be able to improve and optimize other factors such as physical, psychological, social and academic aspects.Keywords : social support; students; adjustment